FEATURES OF UNSTEADY WATER CONNING REGARD TO THE GAS WELLS OPERATION IN LAYERS WITH BOTTOM WATER - Кондрат, Олександр Романович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
One of the major complications in the design of bottom water-drive gas reservoir associated with the bottom water cones formation was considered. The analysis of theoretical, laboratory and experimental research results on the water conning issues showed that some aspects of the process have been studied insufficiently. Conducted study using 3D computer modeling of multiphase staged filtration task with cyclic, periodic wells operation showed joint feasibility of gas and related formation water extraction from the wells, which eventually leads to higher values of final gas recovery factor. Also the possibility of increasing gas recovery factors from the gas fields with bottom water was investigated, which include the joint selection of gas and water from the wells.